Genetic diversity among natural populations of Keteleeria evelyniana mast. In central higlands of Viet Nam using SSR markers - Lieu, Tran Thi; Hien, Vu Thi Thu; Phong, Dinh Thi (Vietnam Journal of Science and Technology, 2018)
Keteleeria evelyniana Mast. is a big softwood species with high economic values. Therefore, the number of these trees are rapidly decreasing due to rampant exploitation as well as its habitat loss and recently, the species is considered vulnerablein Vietnam. In this study, we assessed the genetic variation among seventy K. evelyniana samples of three natural populations in Lam Dong, Dak Lak and Kon Tum using 16 microsatellite markers. The results showed that thirteen markers were polymorphic. A total 39 DNA fragments were amplified, among them, thirty – five were polymorphic (accounting for 89.74%). Among studied populations, the level of genetic diversity at Lam Dong (Na = 2.063; Ne = 1.730; Ap = 0.375; I = 0.558; Ho = 0.459 and He = 0.367) was the highest. Analysis of molecular variance (AMOVA) showed that the total level of molecular changes between populations was 34.65% and between individuals in the same population was 65.35%. Private alleles (Ap) and inbreeding values (Fis) of K. evelyniana species were founded of all three populations in Lam Dong, Dak Lak and Kon Tum (0.375 and -0.234; 0.188 and -0.065; 0.063 and -0.047, respectively). The gene flow (Nm) also occurred among the K. evelyniana populations with the average of Nm = 5.423. A dendrogram (UPGMA) constructed based on the similarity matrix of 70 K. evelyniana samples divided into two main groups with their genetic similarity coefficient ranged from 76.5% (Ke26 and Ke44) to 99% (Ke23 and Ke25). The obtained results indicated the importance of conserving the genetic resources of K. evelyniana species in Tay Nguyen.